2017
DOI: 10.1186/s12889-017-4711-z
|View full text |Cite
|
Sign up to set email alerts
|

Big hearts, small hands: a focus group study exploring parental food portion behaviours

Abstract: BackgroundThe development of healthy food portion sizes among families is deemed critical to childhood weight management; yet little is known about the interacting factors influencing parents’ portion control behaviours. This study aimed to use two synergistic theoretical models of behaviour: the COM-B model (Capability, Opportunity, Motivation – Behaviour) and Theoretical Domains Framework (TDF) to identify a broad spectrum of theoretically derived influences on parents’ portion control behaviours including e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 75 publications
1
31
0
Order By: Relevance
“…Parents felt that nurses assumed parental knowledge on BMI and childhood overweight management and that parental understanding on the issue was rarely examined. The findings of this study are supported by Curtis, Atkins, and Brown () who suggest that parents find it difficult to quantify portion sizes for children and lack knowledge and skills in this area. This highlights the need for greater nurse understanding of parental health literacy on this topic and how poor parental, family and community health literacy impacts on child health outcomes (Nutbeam, ), including childhood obesity (Chari, Warsh, Ketterer, Hossain, & Sharif, ).…”
Section: Discussionsupporting
confidence: 79%
“…Parents felt that nurses assumed parental knowledge on BMI and childhood overweight management and that parental understanding on the issue was rarely examined. The findings of this study are supported by Curtis, Atkins, and Brown () who suggest that parents find it difficult to quantify portion sizes for children and lack knowledge and skills in this area. This highlights the need for greater nurse understanding of parental health literacy on this topic and how poor parental, family and community health literacy impacts on child health outcomes (Nutbeam, ), including childhood obesity (Chari, Warsh, Ketterer, Hossain, & Sharif, ).…”
Section: Discussionsupporting
confidence: 79%
“…In previous research, parents struggled with quantifying appropriate portions for children and adjusting portions was considered effortful and inconvenient (Curtis et al . ). Evidence from a qualitative study by Blake et al .…”
Section: Downsizing For Children Adolescents and Familiesmentioning
confidence: 97%
“…It will be interesting to discover whether these strategies are acceptable. In previous research, parents struggled with quantifying appropriate portions for children and adjusting portions was considered effortful and inconvenient (Curtis et al 2017). Evidence from a qualitative study by Blake et al (2015) of 60 low-income families found that portion size control strategies used by parents included using small containers and measuring cups to subdivide large portions and purchasing small pre-packaged snacks.…”
Section: Downsizing For Children Adolescents and Familiesmentioning
confidence: 99%
“…However, parents also describe these efforts as inconvenient, often relying on pre‐packaged items to determine the appropriate amount to serve children (Curtis et al . ). As packages for HED snacks are generally developed with adults in mind, an appropriate portion size for a child may indeed involve downsizing the contents of the pack.…”
Section: Downsizing Snacks For Young Childrenmentioning
confidence: 97%